Experimental testing on the influence of shaft rotary lip seal misalignment for a marine hydro-kinetic turbine. (March 2022) - Hand, Brian P.; Erdogan, Nuh; Murray, Dónal; Cronin, Patrick; Doran, John; Murphy, Jimmy
Abstract: Tidal energy has received considerable attention over the past decade due to its predictability and high power density. The research in the tidal turbine area has concentrated primarily on the improvement of the energy conversion efficiency. In contrast, the testing of the tidal turbine's mechanical components has received less attention. In particular, the reliable operation of rotary seals is crucial to prevent water ingress into mechanical and electrical components. This paper outlines an experimental test campaign to investigate the effect of shaft misalignment. Both instantaneous temperature and pressure measurements were recorded from two rotary seals. It was shown the temperature inside the aligned seal increased until the seal chamber pressure became equal with the inlet water pressure. The wear on the lip seal rings was examined and the difference found to be between 3.28% and 19.61%. Inspection of the seal liners, showed the presence of strong wiping effects for the misaligned seal with maximum track width differences of between 52.94% and 97.60% being noted. The misaligned seal liner experienced wider wear tracks but were not as deep as the aligned seal with differences of between 37.55% and 103.13% being recorded.